Nomadic Enhancers: Tissue-Specific cis-Regulatory Elements of yellow Have Divergent Genomic Positions among Drosophila Species - Kalay, Gizem; Wittkopp, Patricia J. (PLoS genetics, 2010)
cis-regulatory DNA sequences known as enhancers control gene expression in space and time. They are central to metazoan development and are often responsible for changes in gene regulation that contribute to phenotypic evolution. Here, we examine the sequence, function, and genomic location of enhancers controlling tissue- and cell-type specific expression of the yellow gene in six Drosophila species. yellow is required for the production of dark pigment, and its expression has evolved largely in concert with divergent pigment patterns. Using Drosophila melanogaster as a transgenic host, we examined the expression of reporter genes in which either 5' intergenic or intronic sequences of yellow from each species controlled the expression of Green Fluorescent Protein. Surprisingly, we found that sequences controlling expression in the wing veins, as well as sequences controlling expression in epidermal cells of the abdomen, thorax, and wing, were located in different genomic regions in different species. By contrast, sequences controlling expression in bristle-associated cells were located in the intron of all species. Differences in the precise pattern of spatial expression within the developing epidermis of D. melanogaster transformants usually correlated with adult pigmentation in the species from which the cis-regulatory sequences were derived, which is consistent with cis-regulatory evolution affecting yellow expression playing a central role in Drosophila pigmentation divergence. Sequence comparisons among species favored a model in which sequential nucleotide substitutions were responsible for the observed changes in cis-regulatory architecture. Taken together, these data demonstrate frequent changes in yellow cis-regulatory architecture among Drosophila species. Similar analyses of other genes, combining in vivo functional tests of enhancer activity with in silico comparative genomics, are needed to determine whether the pattern of regulatory evolution we observed for yellow is characteristic of genes with rapidly evolving expression patterns.